Level of Awareness through Marketing Promotional Efforts: A Study on Biotechnology Program among Pre-University Students in Malaysia - Lim, Tiffeny Ai Ji (2013)
This thesis is an exploratory study that emphasize on the pre-university student’s awareness and through marketers’ promotional efforts about biotechnology programme. It is evident from the literature that important of marketers’ promotional efforts and awareness has been heightened. The thesis will take an outlook on the biotechnology sector, especially in biotechnology education subdivision. Consequently, the objectives of this study are to assess the pre-university students’ awareness in biotechnology programme and to identify the factors that influence the awareness. Under the umbrella of promotional efforts there are 7 factors that act as the independent variables, which are performance effect (PE), recognisability (R), communication (C), promotional management (PM), sales performance effect (SP), coast effect (CE) and lastly support effect (SE). In meantime, awareness (AW) will be the lead role as dependent variable. To achieve this objective, quantitative approach will be used with questionnaire as a tool. Smart PLS software was utilized to run reliability, validity as well as hypothesis test in order to examine relationship among constructs. The outcome of the study indicated five factors were significant out of seven, which are PE, R, C, PM, and SE. Moreover, PM was perceived to be the most significant factor that influences awareness among pre-university students about biotechnology programme.